KNOWLEDGE AND PRACTICES REGARDING PREVENTION OF HEPATITIS B, C & HIV AMONG HEALTHCARE WORKERS RELATED TO HOSPITAL WASTE DISPOSAL OF LAHORE GENERAL HOSPITAL - Abdul Hanan; Sania Muneer; Hina Dawood; Nosheen Mustafa (International Journal of Pharmacy & Integrated Health Sciences)
Background: Waste produced in healthcare may contain infectious material such as hepatitis B, C, and HIV. It carries a risk to healthcare workers if it is managed poorly. Objectives: Our study aims to assess the knowledge and practices regarding the prevention of hepatitis B, C, and HIV among healthcare workers related to hospital waste disposal. Methodology: It is a cross-sectional descriptive study, with a sample size of 100, conducted among healthcare workers related to hospital waste disposal at Lahore General Hospital. Results: 91% knew about hepatitis B and C. 70% knew it is transmitted via body fluids/blood. 81% knew vaccines prevent it. 71% knew proper disposal of syringes is required for prevention. 58% knew avoiding multiple partners is a method of prevention. 64% had received vaccination for hepatitis B. Regarding AIDS, 78% knew about it. 41% knew that it was a viral disease. 57% knew it is transmitted from unsterilized equipment, and 63% knew it is transmitted from blood/body fluids. 25% had a test for HIV. 88% knew about the color-coding system. 90% wear a head cap, gown, and gloves while handling waste. Conclusions: According to our research, we concluded that those waste management workers who have knowledge about Hepatitis B, C, and HIV and the spread of diseases through hospital waste are cautious about direct contact with the waste, are using protective clothing (masks, gown, gloves, and caps) and are vaccinated.